Suggestions on proper circular frequencies establishing for the sucker rod pumping units - Rusu, L.; Popovici, A. (NTU "KhPI", 2009)
There are comparatively analysed many methods of determining the fundamental circular frequency of a column of sucker rods with sectioned geometry, for a rod pumping unit and there are given utilisations recommendations.
Предложения по требуемому установлению частот для насосных единиц
Keywords: proper circular frequencies; rod pumping units